2021
DOI: 10.3390/nu13124304
|View full text |Cite
|
Sign up to set email alerts
|

Cord Blood Manganese Concentrations in Relation to Birth Outcomes and Childhood Physical Growth: A Prospective Birth Cohort Study

Abstract: Gestational exposure to manganese (Mn), an essential trace element, is associated with fetal and childhood physical growth. However, it is unclear which period of growth is more significantly affected by prenatal Mn exposure. The current study was conducted to assess the associations of umbilical cord-blood Mn levels with birth outcomes and childhood continuous physical development. The umbilical cord-blood Mn concentrations of 1179 mother–infant pairs in the Sheyang mini birth cohort were measured by graphite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Manganese (Mn), as one of the essential trace elements, may play a vital role in fetal growth and development [ 3 , 4 , 5 , 6 ]. A national nutrition and health survey in the United States showed that the blood Mn concentration of pregnant women was higher than that of non-pregnant women, suggesting that Mn plays an essential role in pregnancy [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Manganese (Mn), as one of the essential trace elements, may play a vital role in fetal growth and development [ 3 , 4 , 5 , 6 ]. A national nutrition and health survey in the United States showed that the blood Mn concentration of pregnant women was higher than that of non-pregnant women, suggesting that Mn plays an essential role in pregnancy [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…This concept has been proposed in the 'Developmental Origins of Health and Disease (DOHaD)' hypothesis [3,4]. Numerous human biomonitoring studies have shown the wide exposure of pregnant women and their fetuses to numerous chemical families via the measurement of the concentration of chemicals in the maternal blood during pregnancy and/or in the umbilical cord at delivery [5][6][7]. In addition to environmental exposures, most pregnant women will likely be exposed to therapeutic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al [12] also examined the association between maternal exposure to vanadium, chromium, manganese, cobalt, nickel, and selenium in early pregnancy and the risk of GDM, and found that vanadium was positively associated with the risk of GDM, while nickel was negatively associated. Dai et al [13] reported that prenatal manganese exposure was negatively correlated with childhood physical development, which appeared to be most significant in the early stages. These studies emphasized the importance of detecting the concentrations of trace elements during pregnancy.…”
mentioning
confidence: 99%